2019
DOI: 10.1002/ijc.32138
|View full text |Cite
|
Sign up to set email alerts
|

LIPG‐promoted lipid storage mediates adaptation to oxidative stress in breast cancer

Abstract: Endothelial lipase (LIPG) is a cell surface associated lipase that displays phospholipase A1 activity towards phosphatidylcholine present in high‐density lipoproteins (HDL). LIPG was recently reported to be expressed in breast cancer and to support proliferation, tumourigenicity and metastasis. Here we show that severe oxidative stress leading to AMPK activation triggers LIPG upregulation, resulting in intracellular lipid droplet accumulation in breast cancer cells, which supports surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 42 publications
1
34
1
Order By: Relevance
“…Upregulation of LIPG has been reported as a mechanism for accommodating elevated level of reactive oxygen species (ROS) (32). Enrichment of oxidative phosphorylation pathway ( Fig.2A) Research.…”
Section: Endogenous Lipg Is Critical For Proliferation and Chemo-resimentioning
confidence: 98%
“…Upregulation of LIPG has been reported as a mechanism for accommodating elevated level of reactive oxygen species (ROS) (32). Enrichment of oxidative phosphorylation pathway ( Fig.2A) Research.…”
Section: Endogenous Lipg Is Critical For Proliferation and Chemo-resimentioning
confidence: 98%
“…Predicting prognosis and response to therapy remains a challenging task (Hellwig et al, 2016[ 14 ]; Lohr et al, 2015[ 18 ]; Weisner et al, 2019[ 28 ]) with many modifying factors, e.g. proliferation (Siggelkow et al, 2012[ 26 ]), antioxidative status (Cadenas et al, 2010[ 4 ], 2014[ 5 ], 2019[ 6 ]) and metabolism (Marchan et al, 2017[ 19 ]; Stewart et al, 2012[ 27 ]) playing an important role. The present study of Edlund and colleagues helps to gain an overview which key factors modify the prognostic role of tumor infiltrating lymphocytes.…”
Section: mentioning
confidence: 99%
“…Recently, Cadenas and colleagues reported that the endothelial lipase (LIPG) is upregulated during oxidative stress and supports survival of cells that are no longer able to generate a sufficient supply of fatty acids by de novo synthesis (Cadenas et al, 2019[ 3 ]). LIPG is a cell surface associated lipase that cleaves phosphatidylcholine from high-density lipoproteins (Jaye et al, 1999[ 10 ]; Choi et al, 2002[ 5 ]).…”
Section: mentioning
confidence: 99%
“…In the present study, Cadenas and colleagues used overexpression and knockdown strategies to demonstrate that LIPG enables breast cancer cell lines to utilize circulating lipoproteins to synthetize and store triglycerides in lipid droplets (Cadenas et al, 2019[ 3 ]). Moreover, the authors showed that oxidative stress under conditions that block endogenous fatty acid synthesis induces LIPG expression and activity.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation